Strategi pengembangan UMKM Bakso Wijaya Arema melalui Business Model Canvas di Kabupaten Pamekasan - Andriansyah, Muhammad Nizar; Nugroho, Taufik Rizal Dwi Adi; Destiarni, Resti Prastika (Universitas Trunojoyo Madura, 2025)
The Bakso Wijaya Arema Micro, Small, and Medium Enterprise (MSME), established in 2007, faces fundamental operational and developmental challenges. Key issues include an unrepresentative sales location, lack of structured financial records, absence of branches, and suboptimal promotion. Internally, the MSME exhibits weaknesses in market segmentation understanding, a lack of clear value proposition, and manual financial management. This research aims to formulate a comprehensive development strategy for Bakso Wijaya Arema MSME in Pamekasan Regency by evaluating its existing business model and enhancing marketing, promotion, and overall performance. Employing a descriptive qualitative approach, data was collected through observation, interviews, and documentation. Analysis utilized the Business Model Canvas (BMC) to describe the business model and identify influencing factors, along with SWOT analysis (IFAS and EFAS matrices) to pinpoint strengths, weaknesses, opportunities, and threats. Findings position the MSME in Quadrant III (W-O) of the SWOT matrix (IFAS = -1.06; EFAS = 9.17), indicating significant internal weaknesses alongside substantial external opportunities. Consequently, a Weaknesses-Opportunities (W-O) strategy is recommended, focusing on leveraging these opportunities to overcome internal deficiencies. Proposed strategies include developing digital distribution channels, partnering with online ride-hailing services, enhancing product value through innovation, implementing promotions and discounts, establishing dedicated digital marketing and customer relations divisions, and transitioning to more accurate and efficient digital financial management. These strategies seek to expand market reach, boost competitiveness, and address internal weaknesses by capitalizing on external opportunities.